Technical considerations for co-locating UWB and GPS radios - Van Slyke, Tyler H. (Kansas State University, 2009)
Excitement about using ultra-wideband (UWB) technology for networking has grown considerably over the last few years. UWB has several strengths, including high data rates, security, and robustness in multipath environments. Despite these benefits, UWB has been scrutinized for its potential to interfere with narrowband technologies like the Global Positioning System (GPS). Until recently, much of the literature about UWB and GPS compatibility has been published on the basis of theoretical analysis alone. We have investigated the compatibility of UWB and GPS signals using theoretical analysis as well as laboratory measurements with a consumer GPS receiver and a WiMedia UWB device. We conclude from our tests that the UWB device does emit interference in the GPS L1 band, but the interference is low enough that careful antenna and chipset placement could allow UWB and GPS radios to coexist in a single product. Also, we have evaluated several UWB antennas to determine their fitness for use in a handheld electronic product. We find that the antennas’ gain pattern and return loss do not have a significant effect upon the data throughput of the UWB system. Thus, we infer that the indoor environment is highly dispersive and that the UWB system is able to exploit multipath propagation. Furthermore, we have created a link budget to estimate the distances over which a WiMedia UWB system should be capable of operating. In the lab, the maximum distances over which the UWB device actually operated were about half of what we expected. This suggests that the path loss exponent and standard deviation of fading could be higher than we expected or that the implementation loss of the UWB chipset is quite high. Currently the market potential of UWB is uncertain. If UWB is embraced by the consumer electronics industry as the wireless platform of choice for Certified Wireless USB and high-speed Bluetooth technology, it could become a ubiquitous networking feature for electronic products such as phones, laptops, cameras, media players, and portable navigation devices. In this thesis, we strive to provide information that would be useful when undertaking a GPS and UWB radio integration project.
Keywords: UWB; GPS; interference; coexistence; Engineering, Electronics and Electrical (0544)